Coffea liberica leaf and tree architecture model of confusing accession in Poncokusumo, Malang District, East Java, Indonesia - ERONA WAFARETTA; YOGA DWI JATMIKO; WENNY BEKTI SUNARHARUM; LUCHMAN HAKIM (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Wafaretta E, Jatmiko YD, Sunarharum WB, Hakim L. 2023. Coffea liberica leaf and tree architecture model of confusing accession in Poncokusumo, Malang District, East Java, Indonesia. Biodiversitas 24: 3073-3080. Some Coffea liberica W.Bull varieties appear in the same garden with the same planting pattern in the Poncokusumo. This could be due to differences in tree architecture from one accession to another. This research aims to identify the architectural and morphological characteristics of C. liberica stems and leaves and determine differences in coffee variety accession through morphological differences in C. liberica plants and leaf architecture. The research was conducted from July 2021 to August 2022 in the C. liberica plantation in Poncokusumo Sub-district, Malang District, East Java, Indonesia. The research sample consisted of four C. liberica trees from each accession and was carried out in four stages: observation, data/image recording, measurement, and data analysis. This research found: each accession has a different plant architecture model and a different branching model; three accessions appear to have different leaf morphological characters, namely margin type, apex angle, and base angle; dendrogram and PCoA results show that each accession has significant differences. Further research at the genetic level and the effect of abiotic or biotic elements on the growth and development of this coffee tree is necessary to enlighten the C. liberica variety's high potential for the growth of this coffee production in the local community.